Impact of Photography on the Representation of The George Town Heritage Site in Penang, Malaysia - Farhad Fakhrian Roghani,; Zainurul Rahman, (Wacana Seni Journal of Arts Discourse, 2017)
This study, along with its practical implementation, intended to combine art with the characteristics of applied photography to draw public attention to the unseen or neglected values of the George Town Heritage Site. The researcher, as an experienced professional commercial photographer and artist, took several photographs of the eroded walls of George Town and installed each large-scale photograph on the same wall that they portrayed to create a piece of art. This street photography exhibition was held for one month, during which the researcher conducted in-depth interviews with 43 local and foreign respondents who visited the exhibition. The study utilised qualitative art practice based on judgment sampling and semi-structured interviews as its research methodology. Results show that the project is unique and similar exhibitions do not exist.